2017
DOI: 10.18520/cs/v112/i02/348-354
|View full text |Cite
|
Sign up to set email alerts
|

Submagmatic Fabric in the 2.6 Ga Bundelkhand Granitoid, India:Evidence from Microstructure

Abstract: Primary foliations in igneous rocks are the key to understanding processes within the magma chamber, cooling history, paleostress regime and strain during emplacement of granitoid plutons. In the 2.6 Ga Bundelkhand granitoid rocks, weak to moderately strong regional fabric is the result of submagmatic grainsupported flow during syn-kinematic emplacement of the magma. Microstructural and outcrop-scale evidences provide an excellent record for interpreting the significance of this fabric development vis-à-vis rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Instead of considering the red and grey granitoids are of separate entities, Sensarma et al (2018) suggested that the original grey-coloured granitoid transformed to red-coloured granitoid due to mantle-derived high temperature fluid-rock metasomatic alteration. The conclusion of Sensarma et al (2018) is further supported by the observation that both grey-and red-coloured granitoids show similar modal mineralogical compositions (Sarkar et al 2017) and contemporaneous crystallisation age (Kaur et al 2016). We, therefore, use the common term granitoid to refer to both red-and grey-coloured granitoid rocks that exhibit an undoubtedly porphyritic texture under the microscope (figure 1c).…”
Section: General Characters Of the Bgmentioning
confidence: 63%
“…Instead of considering the red and grey granitoids are of separate entities, Sensarma et al (2018) suggested that the original grey-coloured granitoid transformed to red-coloured granitoid due to mantle-derived high temperature fluid-rock metasomatic alteration. The conclusion of Sensarma et al (2018) is further supported by the observation that both grey-and red-coloured granitoids show similar modal mineralogical compositions (Sarkar et al 2017) and contemporaneous crystallisation age (Kaur et al 2016). We, therefore, use the common term granitoid to refer to both red-and grey-coloured granitoid rocks that exhibit an undoubtedly porphyritic texture under the microscope (figure 1c).…”
Section: General Characters Of the Bgmentioning
confidence: 63%
“…To determine the relative proportions of dominant mineralogy including different types of feldspar and to ascertain interrelation between the red colouration and primary modal abundance of feldspar types in these granitoids, modal analyses of both grey and red granitoids were done (see fig. 2 in Sarkar et al, ). It is important to note that both grey and red granitoids fall in the monzogranite field, except for limited samples, which plot as granodiorite and syeno‐granite and thus could not be petrographically discriminated.…”
Section: Resultsmentioning
confidence: 96%
“…Large euhedral to subhedral feldspar crystals and relatively smaller grained quartz and mafic ferromagnesian minerals (in variable proportions <10%) constitute the granitoids. The inequidimensional and elongated tabular feldspar crystals and ferromagnesian minerals are preferentially arranged imparting a weak submagmatic fabric (Sarkar et al, ), which gives a crude apparent gneissic appearance to the rocks. Under the microscope, green‐coloured microveins are abundantly and intricately present particularly along grain boundaries, fractures, and cleavage planes in the feldspars in the red granitoids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations